Glial Derived TGF-β Instructs Axon Midline Stopping - Marmor-Kollet, Neta (Front Mol Neurosci, 2019)
A fundamental question that underlies the proper wiring and function of the nervous system is how axon extension stops during development. However, our mechanistic understanding of axon stopping is currently poor. The stereotypic development of the Drosophila mushroom body (MB) provides a unique system in which three types of anatomically distinct neurons (γ, α’/β’, and α/β) develop and interact to form a complex neuronal structure. All three neuronal types innervate the ipsi-lateral side and do not cross the midline. Here we find that Plum, an immunoglobulin (Ig) superfamily protein that we have previously shown to function as a TGF-β accessory receptor, is required within MB α/β neurons for their midline stopping. Overexpression of Plum within MB neurons is sufficient to induce retraction of α/β axons. As expected, rescue experiments revealed that Plum likely functions in α/β neurons and mediates midline stopping via the downstream effector RhoGEF2. Finally, we have identified glial-derived Myoglianin (Myo) as the major TGF-β ligand that instructs midline stopping of MB neurons. Taken together, our study strongly suggests that TGF-β signals originating from the midline facilitate midline stopping of α/β neuron in a Plum dependent manner.